A novel supramolecular system with multiple fluorescent states constructed by orthogonal self-assembly. Issue 23 (12th May 2016) - Dong, Qingchen; Qu, Wenshan; Wang, Pi; Wong, Wai-Yeung
Abstract : A novel supramolecular fluorescent system was successfully constructed by orthogonal self-assembly of host–guest and metal–ligand interactions. By controlling the non-covalent interactions in different ways, the system exhibits diverse fluorescent switching phenomena. Abstract : A novel supramolecular fluorescent system was successfully constructed by orthogonal self-assembly of host–guest and metal–ligand interactions. By controlling the non-covalent interactions in different ways, the system exhibits diverse fluorescent switching phenomena.